Outside Back Cover: Volume 1 Issue 1. Issue 1 (31st January 2022) - Unknown
Abstract : Outside Back Cover : Single atoms, atomic clusters and nanoparticles emerge as three basic building blocks of catalysts featuring quite different chemical properties. When nurturing their marriages in one catalytic entity aims at catalyzing the complex electrochemical reaction in one specific route, they present an unpredicted yet amazing interaction, which is analog to "three body" problem. In article number idm212011, John Wang, Zongkui Kou and co‐workers define their combination and review the recent achievements by respectively discussing the marriages of single atoms with single atoms, atomic clusters, and nanoparticles as case studies. To rationally design these binary combinations, new mechanism understanding, dynamic features with multiscale methodologies are also discussed.